Potential of membrane technology for treatment and reuse of water from old mining lakes - Teow, Yeit Haan; Abdul Wahab Mohammad,; Syazaman Ramli,; Mohd Shaiful Sajab,; Noorini Izzati Mohamad Mazuki, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The El-Nino phenomenon in early 2014 contributed to the lack of water supply in most Southeast Asian countries. Suggestions have since been made to ensure the continuity of water supply, one of which involves membrane technology to treat mine water so that it is compatible for citizens’ use. Accordingly, the objective of this research was to study the efficiency of membrane technology in treating mine water. Our elucidation of all the parameters has showed that the best attainable classification is at Class IV. Although it was still regarded as polluted, the treated mine water can be used as water supply reservoir. For the membranes tested such as ultrafiltration 10 kDa, 5 kDa and reverse osmosis, the percentage of rejection for chemical oxygen demand is 21-72%, 40-96% for total suspended solids and 21-72% for ammonia nitrogen. The pH also gradually shifted to almost neutral after the filtration.